Time in therapeutic range for targeted temperature management and outcomes following out-of-hospital cardiac arrest. (January 2023) - Wheelock, Kevin M; Chan, Paul S; Chen, Lian; de Lemos, James A; Miller, P Elliott; Nallamothu, Brahmajee K; Girotra, Saket; Khera, Rohan
Abstract: Objective: For comatose survivors of out-of-hospital cardiac arrest (OHCA), current guidelines recommend targeted temperature management (TTM) with a goal temperature of 32 °C–36 °C for at least 24 h. We examined adherence to temperature targets, quantified as time-in-therapeutic range (TTR), and association of TTR with survival and neurologic outcomes. Methods: We conducted a retrospective cohort study of the Resuscitation Outcomes Consortium-Continuous Chest Compressions trial, including adults with OHCA who underwent TTM for >12 h. We imputed continuous temperatures between consecutive temperature measurements using the linear interpolation method and calculated TTR for multiple target temperatures. The association of TTR with survival to hospital discharge and favorable neurological outcome was evaluated using hierarchical regression models. Main results: Among 2, 637 patients (mean age 62.3 years, 29.9 % female), the median duration of TTR for TTM between 32 °C–36 °C was 23 (IQR: 21–24) hours with a median time outside therapeutic range of 0.9 (IQR: 0.0–4.2) hours. In risk-adjusted analyses, there was no association of TTR of 32 °C–36 °C with overall survival (OR 1.00 [95 % CI, 0.90–1.10]) or favorable neurologic outcome (1.02 [95 % CI, 0.90–1.14]). However, in assessments of TTR 33 °C–36 °C, there was a significant association with favorable neurologic survival (OR 1.12 [1.01–1.25]) but not overall survival (OR 1.04 [0.94–1.15]). Conclusions: Among patients with OHCA who underwent TTM, we found variability in adherence to guideline-recommended treatment targets. Higher TTR was not associated with overall survival, but for certain temperature thresholds, TTR was associated with favorable neurologic outcome.